Multilateral R&D alliances by new ventures - Li, Dan (Journal of Business Venturing, 2013)
We examine the antecedents and outcomes of new ventures' formation of multilateral R&D alliances. Our results show an inverted U-shaped relationship between market uncertainty and a new venture's likelihood of forming multilateral R&D alliances. Top management team's social capital and ventures' technological capabilities are critical for new ventures to identify and capture alliance opportunities. Moreover, our analysis reveals value creation effects of multilateral R&D alliances for new ventures despite the challenges and difficulties associated. We further show that the value creation effect is a function of the type of exchange relationship (i.e., net- vs. chain-based) in the multilateral R&D alliance and that governance structure moderates this relationship.